A study of high-nuclear-grade breast cancer in Thailand: Subclassification and correlation with prognostic factors and immunohistochemical study - Benjaporn Chaiwun (2018)
Objectives: To classify high-nuclear-grade breast cancer (BC) into typical medullary carcinoma (TMC), atypical medullary carcinoma (AMC), and non-medullary carcinoma (NMC), and luminal A, luminal B, and HER2, and to correlate these tumors with other prognostic factors. Materials and methods: A retrospective study reviewing high-nuclear-grade BCs. The patients' age, histologic types, various histologic features, axillary lymph node (ALN) status, and results of immunohistochemical (IHC) study were recorded and analyzed. Results: One-hundred and eighty-one cases of high-nuclear-grade BCs were reviewed and categorized into IDC, NOS (140, 77.3%), TMC (1, 0.6%), AMC (21, 11.6%), and others (19, 10.5%). The median age was younger in AMC than in NMC patients. NMC patients had a higher incidence of LVI and ALN metastasis with involvement of more than four lymph nodes (p = 0.006) whereas AMC patients had a higher mitotic index. Forty-six (35.9%) cases were triple-negative (TN), including 1 (100%), 7 (53.9%) and 38 (33.3%) cases of TMC, AMC, and NMC, respectively. AMC had a significantly lower number of node metastases (p = 0.006) than NMC; whereas TN had higher MI (p = 0.001) than non-TN. The non-TN group was subclassified into luminal A, luminal B, and HER2. Of these, TN and luminal B occurred at younger age (p = 0.01) whereas TN and luminal A had a higher mitotic count. TN had lower incidence of LNM including higher number of LNM. Conclusion: Overall, AMC-TN group showed a basal-like prognostic factor expression. NMC may be separated into TN and non-TN, with possibly different behavior. These sub-groupings should continue to be used. Interestingly, luminal A in our study tended to correlate with poor prognostic factors, thus, luminal A with high nuclear grade may not be representative of the usual luminal group profiles. © 2009 The Japanese Breast Cancer Society.